PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR MATEMATIKA - Akbar, Ali (Universitas PGRI Adi Buana Surabaya, 2015)
Teacher must always has many creation for every lesson to make the different situation. Find the way how to rise the motivation of learning result is the main task which do for the purpose learning to be fun and satisfying of learning result. This is the role of teacher as a motivator, so the writer provides decriptive quantitative research with the title “The Influence Of Cooperative Learning Method Two Stay Two Stray (TSTS) Type To The Result Of Mathematics Learning Student 2014/2015”. The problem of the research is what is the influence of cooperative learning method Two Stay Two Stray (TSTS) type to the result of mathematics student of class VII SMPN 1 Wonoayu. “Therefore, the purpose of this research is to know whether or not the influence of learning method to the result of learning mathematics student of class VII SMPN 1 Wonoayu”.after the result of research has t observed > t table is 3,514 > 1,666witha significance level of0.001 (a = 0,05 ). The result of post test control class lesser 75,75 than experiment class 61,81, so that the conclusion is there are the influence of learing method to the result of learning mathematics student of class VII SMPN 1 Wonoayu 2014/2015 school year. Keywords: Two Stay Two Stray, the result of mathematics learning